2021
DOI: 10.1021/acsanm.1c01880
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Dynamics in Carbon Dots as Photosensitizers: A Review

Abstract: Electron transfer (ET) is an ultimate property of chemical and biological processes and photochemistry, which is the root of the world. Thus, photoinduced electron transfer (PET) is a fundamental focus of modern research applied in biosensing, solar energy conversion, optoelectronics, and photocatalysis, where light-induced charge separation takes place within the reaction system. The reaction system is made by the combination of a photosensitizer, an electron donor or acceptor, and photocatalysis to control t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 138 publications
0
11
0
Order By: Relevance
“…[18][19][20] The extremely easy synthetic and purification methods of CDs have made them useful in analytical applications, 21 light harvesting, 22 photocatalysis, 23,24 solar cells, 25,26 designing molecular logic gates, 27 and photosensitization. [28][29][30] The photosensitive CDs are also useful in treating cancer by photodynamic therapy (PDT). 31,32 FRET with CDs were utilized in DNA 33 as fluorescent reporters in the micellar and reverse micellar cavities, and surfactant and lipid bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] The extremely easy synthetic and purification methods of CDs have made them useful in analytical applications, 21 light harvesting, 22 photocatalysis, 23,24 solar cells, 25,26 designing molecular logic gates, 27 and photosensitization. [28][29][30] The photosensitive CDs are also useful in treating cancer by photodynamic therapy (PDT). 31,32 FRET with CDs were utilized in DNA 33 as fluorescent reporters in the micellar and reverse micellar cavities, and surfactant and lipid bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…The excitation-emission maps, therefore, indicate that both the starting material (chestnut or peanut) and the way in which the material is treated (H2O or NH4OH as dispersing medium) influence the excitation-wavelength-dependent emission of C-dots and can, therefore, be used to tune their properties. It has been widely reported in the literature that the photoluminescent properties of C-dots depend on their surface emissive states [28,43]; therefore, both the starting material and the dispersion solvent must have influ- The normalized excitation-emission maps reveal that the C and P C-dot samples have different photophysical behaviours. While P H 2 O and P NH 4 OH have a markedly red-shifted excitation-dependent emission (λ exc /λ em : 340 nm/450 nm), this feature is less pronounced for the C NH 4 OH and C H 2 O samples, whose excitation and emission maxima are at lower wavelengths (λ exc /λ em : 320 nm/420 nm).…”
Section: Excitation-emission Mapsmentioning
confidence: 99%
“…Numerous reports are available, where metal chalcogenide semiconductors like ZnS, CdS, CdSe, PbS, and PbSe are used to form heterostructures with PQDs that have an enormous impact in tuning the photoresponsivity and luminescence properties. Here, we have prepared a zero–zero-dimensional (0D–0D) nanocomposite integrating the PQDs with the 0-D C-Dots. C-Dots are one of the newcomers in carbon family having unique optical and electrical properties which can be modulated by doping with various non-metallic elements such as boron, phosphorus, sulfur, etc. It is well known that the C-Dots act as an electron donor/acceptor as well as a photosensitizer. The C-Dots have been used for several applications such as metal-free photocatalysis of polymerization, electronics, bioimaging, magnetic resonance imaging imaging, sensing organic molecules or metal ions, and site-specific drug delivery. Recently, Ghosh et al have demonstrated different metal chalcogenide semiconductors and PQD hybrid systems, such as CsPbBr 3 –CdSe and CsPbBr 3 –PbS, and explored the carrier dynamics and charge separation pathways. , In the CsPbBr 3 –PbS hybrid system, the charge-transfer process is bidirectional for hot carriers while exciting at high-energy photons due to the proper alignment of hot carrier states . Brumberg et al reported a comparative study to explore the electronic interactions and the rate of electron transfer between 0D–0D, 0D–2D, and 2D–2D systems using CsPbBr 3 and CdSe .…”
Section: Introductionmentioning
confidence: 99%